Going with the flow: the supply and demand of sediment retention ecosystem services for the reservoirs in Puerto Rico - De Jesus Crespo, R.; Valladares-Castellanos, M.; Mihunov, Volodymyr V.; Douthat, T. H. (Frontiers in Environmental Science, 2023)
Impounding surface waters in reservoirs is a major mechanism for providing water for human consumption, including potable water, hydroelectric power, and industrial uses. Building reservoirs incurs environmental and social costs, and therefore safeguarding their effectiveness and longevity is a concern of clear public interest. One factor that affects the longevity of reservoirs is sedimentation, a process exacerbated by land use conversion in upstream watershed areas. Despite the economic importance of preventing sedimentation in existing reservoirs, few consumers are aware of the natural features that provide sediment retention services and the relevance of their conservation in their daily lives. Moreover, managing for landscape level sediment retention services is challenging due to a lack of clarity regarding supply and demand flows that transcend watershed boundaries and jurisdictions. Our study seeks to bridge these gaps by characterizing the flow of sediment retention services to reservoirs and link these services to the specific consumers that benefit using a socio-ecological network (SEN) framing. We conducted this study on the island of Puerto Rico (PR), the population of which is heavily reliant on reservoirs as a primary water resource, while experiencing severe and chronic reservoir sedimentation problems. Our study models avoided sediment export, and the costs were averted thanks to this service. We characterized protection as opposed to vulnerability of these sediment retention services by estimating the proportion of natural areas under some form of legal conservation status and the level of landscape fragmentation. We frame these services as an SEN by using water distribution lines as links to estimate the number of beneficiaries and their location relative to the reservoir’s water source. Our results identify watersheds with conservation needs, their beneficiaries, and where within those watersheds to prioritize conservation efforts to safeguard access to clean water in PR. More broadly, our study provides a model case study for establishing supply and demand service flows of water purification services and demonstrating the utility of mapping socio-ecological networks of service flows in order to justify conservation policies based on ecosystem services.